In order to see the problem here, you need to refer to following link: http://img.photobucket.com/albums/v224/TurbineSpeed/Picture402887.jpg I understand how they got the expression in the numerator. What I cannot figure out is how they got the denominator. By their math, (x-4)(x+1) + (x+1)(x-4) = (x+1)(x-4) This does not seem correct. Give a value to x such as x = 6, and: (2)(7) + (7)(2) = 14 + 14 = 28 Now if we apply this value to the right member, we get: (7)(2) = 14. 14 is NOT equal to 28. What am I doing wrong???